Let's analyze the steps involved in the equation given.
Starting with:
\[ 3x - 9x + 1 = 2(-3x + 1) - 1 \]
The steps simplify as follows:
-
Combine like terms on the left side: \[ 3x - 9x + 1 = -6x + 1 \]
-
Expand the right side: \[ 2(-3x + 1) - 1 = -6x + 2 - 1 = -6x + 1 \]
So we have: \[ -6x + 1 = -6x + 1 \]
At this point, we see that both sides of the equation are identical:
\[ -6x + 1 = -6x + 1 \]
This implies that the equation is true for any value of \( x \).
Thus, the correct statement from the options provided is:
There are infinitely many solutions to the equation.